Identifikasi Pengalaman Burnout Pekerja Front Office di The Phoenix Hotel Yogyakarta pada Masa Pandemi Covid-19 - Hadi, Muhammad Sofyan (Gadjah Mada Journal of Tourism Studies, 2022)
The front office plays a crucial role in establishing the hotel's reputation in the perception of the customers. Hence, it is imperative to evaluate the efficacy of the front office personnel in order to guarantee client satisfaction during their stay. Nevertheless, as a result of the frequent and intense face-to-face interactions with guests, front office personnel are susceptible to burnout and frequently encounter various stressful situations and demanding expectations. This study aims to ascertain the burnout phenomenon among front office workers at The Phoenix Hotel Yogyakarta amidst the epidemic. The burnout identification in this study pertains to the notion of the Copenhagen Burnout Inventory (CBI) as proposed by Kristensen et al. (2007). This studyutilizes the three dimensions of customer-related burnout in CBI. The research results of a survey yielded several conclusions. First, front office personnel at The Phoenix Hotel Yogyakarta encountered burnout at a relatively low level, with a mean score of 1.98. Second, the results show that 'hard to work with guests' and 'drained energy' are the experiences that received the highest score (χ=2.18). However, the score still indicates a 'low' degree. Meanwhile, the experience that received the lowest scoren was the 'frustration experience' (χ=1.73). The frustration experience is rated as 'very low'.